Targeting anger for COVID-19 prevention: The motivating role of anger on media use and vaccination intention - Yoo Jung Oh; Muhammad Ehab Rasul; Jong In Lim; Christopher Calabrese; Emily McKinley; Hannah Stevens; Monique Mitchell Turner; Maria Knight Lapinski; Tai-Quan Peng (PLoS ONE, 2025)
The COVID-19 pandemic resulted in public anger due to its disruptive and harmful nature. However, anger remains an understudied concept despite its potential to persuade the public and spark action. The current study investigates the role of anger in driving COVID-19 vaccination intentions. In Study 1, through a rolling-cross sectional survey of U.S. adults during the early stages of the COVID-19 epidemic ( N = 6,141), it was found that anger towards COVID-19 was associated with increased use of social and traditional media news, which was then related to improved vaccination intentions. In Study 2, utilizing computational analysis of a Twitter (now X) dataset using an AI classifier, 15 targets of anger were identified from real-world anger expressions in social media discourse about COVID-19. Building on these insights, Study 3 involved a representative survey of U.S. adults during the post-emergency declaration stage of COVID-19 ( N = 1,005). This survey aimed to replicate the findings of Study 1 while incorporating the anger targets identified in Study 2. The results revealed that different targets of anger were associated with vaccination intentions through the consumption of traditional news media. Although social media was a prominent channel for news about vaccination at the beginning of the pandemic, our findings suggest that traditional media news use may be an important link in understanding the relationship between anger and vaccination intentions. Theoretical, practical, and methodological implications are discussed.